2022
DOI: 10.1021/acsearthspacechem.2c00142
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Catalyzed Decomposition of Multifunctionalized Organic Hydroperoxides Derived from the Reactions of Criegee Intermediates with Ethylene Glycol in Aqueous Organic Media

Abstract: Organic hydroperoxides (ROOHs) are ubiquitous, reactive oxygen species that play central roles in atmospheric, environmental, and biological chemistry. Because atmospheric ROOHs possess not only −OOH but in most cases other functionalities such as −C­(O) and −OH, they are expected to reside in condensed phases such as aerosols, fog and cloud droplets, and wet films of leaves and soils. Here, we report a study of the kinetics of the liquid-phase decomposition of multifunctionalized C12 α-alkoxyalkyl hydroperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…276,356 Second, PO hydrolysis is highly influenced by the condensed-phase pH. 125,135,397,399 As indicated in Figure 15, the hydrolysis of α-HAHPs 396,397 and α-AHPs 49,122,125 is catalyzed by acids. Meanwhile, a base-catalyzed aqueous-phase decomposition mechanism was proposed for α-AAHP by Zhao et al 135 In addition, temperature plays a significant role in determining the rate of PO hydrolysis (Figure 15).…”
Section: Po Hydrolysismentioning
confidence: 99%
“…276,356 Second, PO hydrolysis is highly influenced by the condensed-phase pH. 125,135,397,399 As indicated in Figure 15, the hydrolysis of α-HAHPs 396,397 and α-AHPs 49,122,125 is catalyzed by acids. Meanwhile, a base-catalyzed aqueous-phase decomposition mechanism was proposed for α-AAHP by Zhao et al 135 In addition, temperature plays a significant role in determining the rate of PO hydrolysis (Figure 15).…”
Section: Po Hydrolysismentioning
confidence: 99%
“…The mechanism in which a water molecule is incorporated into the α-Tp CIs to form α-HHs, followed by rapid decomposition into the corresponding aldehyde and isomerization into lactols is in agreement with our previous results obtained from negative-ion mass spectrometry. , The fact that the signals attributed to lactols kept increasing even after that of α-HH-Na + had disappeared (Figure A) implies that the aldehyde was MS-silent and acted as a reservoir that slowly isomerized into the lactols (Scheme ). Furthermore, we note the possibility that these lactols were also produced from the decomposition of HP-THP/THF (the conversion of ROOH to ROH) as observed in the cases of α-alkoxyalkyl hydroperoxides , and other ROOH . Based on the fact that the ion signals at m / z 267;269 also appeared in water:CD 3 COCD 3 solvent (see below) and the increase of the signals as a function of time was not correlated with the decay of m / z 283, we concluded that these lactols were not a decomposition product of C 13 SOZs.…”
Section: Resultsmentioning
confidence: 89%
“…Thus, the signals for Levo+2O were assigned to α-hydroxy-hydroperoxides (α-HHs) possessing an −OOH and three −OH moieties that were formed by the reaction of hydroxy peroxy radicals [R(−OH)(−OO • )] with HO 2 . As previous studies have suggested, 27,38,48,49 α-HHs partly decompose into their corresponding carbonyl compounds by releasing H 2 O 2 at pH 3.7 (Scheme 1). Thus, our results suggest that H-abstractions from carbon atoms with an −OH moiety (pathway B) occurred more preferentially (∼84%) than abstractions from carbon atoms with an ether -R-O-R′-moiety (∼16%, pathway A).…”
Section: Mass Spectrometry Of Fenton Oxidation Of Levoglucosan In Watermentioning
confidence: 83%
“…They used 2,5-dihydroxybenzoic acid as the matrix and NaCl or LiCl as the catanizing agent and measured mass spectra up to a reaction time of 1 week. Because our NaCl-MS approach was capable of detecting oligomeric species such as dimers produced by the reactions of sesquiterpene Criegee intermediates with alcohols, any oligomeric products of Levo would have been detected if they had formed. In addition, our UV–vis absorption spectroscopic analyses of the reaction mixtures also provided no evidence of the formation oligomeric products (see section ).…”
Section: Resultsmentioning
confidence: 99%